Practical perspective of humanism: a theatrical experience in the sensitive body of the university student - Barquero Alfaro, Julio (2014)
The purpose of this article focuses on the assessment of the academic year Theatre of the Oppressed: A Practical Perspective of Humanism as an art critic and space given to the student population Geenerales Studies Center. The proposal is accompanied by the theoretical position of Augusto Boal and specific elements of Carlos Taibo and Mattelart experimentation and practice their own course and scope, the academic process is analyzed, its importance and necessity in overcoming literalism and passivity university professional future, with a view of the inherent social commitment to training. The experience of the participant group transforms the conventional conception of theater, this being a generator shaft that promotes social mobilization capacity of individual and collective critical consciousness in the university community, as an expressive instrumentreflective, organizational and recreation, which encourages citizen participation.